Pelatihan Laporan Keuangan UMKM Berbasis Handphone di Pusat Perkampungan Budaya Betawi Setu Babakan - Tyahya Whisnu Hendratni; Mulyadi (SULUH: Jurnal Abdimas, 2020)
The development of technology and information is so rapid bringing changes in the business world today. Technology is a very complex and integrated process because it involves procedures, ideas to provide analysis of a problem, problem solving, and evaluating to achieve a certain goal. For SMEs, an orderly presentation of financial statements is very necessary because based on previous experience many transactions per day are not recorded. The administrative system for recording the financial statements of MSMEs is mostly still manual so there are still many MSME actors who do not have financial reports in running their businesses. Therefore, our community service team of FEB-UP is assisting MSMEs at Betawi Setu Babakan Cultural Village Center in the form of MSME-Based Mobile Financial Report Training. Where Mobile is a communication tool that can be used in preparing financial statements.